Model Arsitektur Pohon Di Sekitar Daerah Aliran Sungai Kecamatan Insana Tengah, NTT - Kamaluddin; Blasius Atini; Emanuel M.Y. Hano’e (Pro-Life, 2024)
Tree architectural models are very urgent in soil and water conservation efforts. The aim of this research is to determine the architectural model of trees around the Central Insana watershed. This research was carried out in May-September 2023. This research used an exploratory survey method with a descriptive approach, namely research carried out by conducting direct observations of plants in the field. Sampling used the purposive sampling method. Plant identification used references from several books and journals. The research results found 21 tree species around the Central Insana watershed with 7 types of tree architectural models. The tree architectural models found were Troll with 8 species, Scarrone with 6 species, Rauh and Aubreville's with 2 species each and Massart, Corner and Mc Clure with 1 species each.